2010
DOI: 10.1177/0748233710369665
|View full text |Cite
|
Sign up to set email alerts
|

Sodium metabisulfite induces lipid peroxidation and apoptosis in rat gastric tissue

Abstract: Sodium metabisulfite (Na( 2)S(2)O(5)) is used as an antioxidant and antimicrobial agent in a variety of drugs and functions as a preservative in many food preparations. This study was performed to elucidate the dose-dependent effects of sodium metabisulfite ingestion on rat gastric tissue apoptotic changes and lipid peroxidation. Forty male wistar rats, aged 3 months were used. They were randomly divided into four groups: control (C), the group treated with Na(2)S(2)O(5) (10 mg/kg; S1), the group treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
4
15
0
3
Order By: Relevance
“…Our result showed that MBS (520 mg/kg/day) given by intragastric intubation for 21 days, significantly increased the level of MDA in the testes of adult rats. This result is consistent with other previous reports (Aydin et al, 2005;Derin et al, 2008;Ercan et al, 2010). The mechanisms of sulfite-induced lipid peroxidation have been shown to involve SO 3 2-oxidation into a sulfite radical (SO 3 .-).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our result showed that MBS (520 mg/kg/day) given by intragastric intubation for 21 days, significantly increased the level of MDA in the testes of adult rats. This result is consistent with other previous reports (Aydin et al, 2005;Derin et al, 2008;Ercan et al, 2010). The mechanisms of sulfite-induced lipid peroxidation have been shown to involve SO 3 2-oxidation into a sulfite radical (SO 3 .-).…”
Section: Discussionsupporting
confidence: 83%
“…Sulfite can cause allergic reactions in humans, produces a variety of toxic effects in animals and may act as co-carcinogen (MacPherson, 2001;Gordon et al, 2004;Ercan et al, 2010). In humans, deficiency of sulfite oxidase, an enzyme which catalyses the oxidative detoxification of sulfite, leads to mental retardation, neurological symptoms such as spastic quadriplegia and early death (Niknahad and O'Brien, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sülfitler, tiamin, askorbik asit, B 12 vitamini ve K vitamini ile reaksiyona girer. Tiaminin sülfitolizisi, vitaminin besin değerini yokettiği için sağlığa zararlı olarak kabul edilir.…”
Section: Gi̇ri̇ş Tanımunclassified
“…Buna ek olarak, mide lezyonları-nın ve apoptozun sodyum metabisülfit ile tetiklendiği gös-terilmiştir. Ghrelin'in ise mide hareketlerini ve boşalmasını artırmak için, stres ve iskeminin neden olduğu mide perfüz-yon yaralanmalara karşı ve sodyum metabisülfit kaynaklı mide hasarında mide mukozasını korumak için etkin olduğu saptanmıştır (11)(12)(13).…”
Section: Metabolizmasıunclassified
See 1 more Smart Citation